How Do Perceived Health Threats Affect the Junk Food Eating Behavior and Consequent Obesity? Moderating Role of Product Knowledge Hiding - Li, Yanxia; Li, Xiaohong; Zhang, Tuanting; Guo, Haixia; Sun, Caili (Frontiers in Psychology, 2022)
The predominant use of junk food in our societies is continuously held responsible for the obese body physiques and overweight among the kids and adolescents. The current supportive environments where organic foods are limited and new processed foods have been brought to the market with more variant tastes and acceptability from the kids and adolescents have diverged their eating patterns. It has significantly contributed to the health issues and growth discrepancies of the users. However, the awareness of the food contents is an important milestone for understanding the risks associated with the usage of junk foods. A quantitative approach has been used in this study to measure the affect of perceived severity, vulnerability and fear on the junk food eating behaviors and ultimately on the obesity. The moderating role of product knowledge hiding has also been measured on the relationship of junk food eating and obesity. Structural equation modeling is used using the software Smart PLS 3 for measuring the hypotheses. The current study has explored the role of perceived severity, vulnerability and the fear of using junk foods which have been found to have negative effect on junk food eating behavior which is positively associated with obesity among the kids and adolescents. Results of the study show that perceived threat has a negative affect the junk food eating behavior of the adolescents. However, the positive relationship of junk food eating behavior with obesity can be decreased if the information about the products is not hidden. This study will be useful for making the consumers aware of the product knowledge hiding of the junk foods used. Moreover, it will help the users in creating understanding of risks allied with the use of junk food which may be addressed in order to avoid obesity issues in the kids and adolescents globally.